(untitled) (The Research of Medical Science Review, 2025)
Background: Eco friendly or Green Dentistry can emerge as vital approach, by effectively designing Dental clinic and using more eco friendly material. This study aims to explore the awareness, attitude and practice of eco friendly dentistry among practitioners in Pakistan. Materials and Methods: A cross sectional study was conducted among the House officers and Trained Dentist across the Pakistan using self-structured questionnaire comprising of 16 close ended questions adopted from reviewing literature and previous research paper. Data collected online through various platforms and 115 responses calculated using WHO calculator. Statistical analysis was performed using SPSS version 27. Results: This study assessed the awareness and adoption of eco-friendly dentistry practices among 115 working dental practitioners. The survey revealed that 57.9% of respondents were familiar with eco-friendly dentistry, while 75.7% recommended its adoption. However, significant gaps were identified, including the use of paper-based records (55.8%), low adoption of natural disinfectants (25.2%), and inadequate recycling practices (20.7%). Furthermore, improper mercury disposal (78.1%) and limited use of reusable materials (45.2%) were noted. Encouragingly, 69.6% of practitioners used LED bulbs, and 62.3% preferred digital patient records. The majority (66.1%) believed eco-friendly practices were cost-effective. Notably, 91.3% emphasized the need for formal education on green practices to enhance sustainable dentistry. Conclusion: This study reveal a positive shift towards sustainable dentistry among dental practitioners in Pakistan and future efforts should focus on implementing Green Dentistry principles into Dental education and practice.